Effect of Different Temperature Regimes on Biology of Bruchid, Callosobruchus maculatus (Fab.) and Curculionid, Sitophilus zeamais (Mots.) - Sravani, B. Lavanya; Thakur, N.S. Azad; Firake, D.M.; Patra, Sandip; Rajesh, T.; Ganesh, E. Sankar (Indian Journal of Hill Farming, 2019)
An experiment was conducted at entomology lab at Division of Crop Protection, ICAR Research Complex for NEH Region and at School of Crop Protection, College of Post Graduate Studies, Umiam, Barapani, Meghalaya to assess the effect of different temperature regimes on biology of bruchid (Callosobruchus maculatus Fab.) and curculionid (Sitophilus zeamais Mots.). These pests cause severe damage to stored grains and thus studies were conducted to understand the effect the four different temperatures ranging from 20 to 35°C on their biology. The developmental period viz., incubation, larval, pupal, adult longevity were found to decrease with increase in temperature in both of these stored grain pests. Preoviposition and oviposition periods showed the similar trend in both the insects studied. However, it was found that fecundity was higher at 30°C in both the insects. Low and higher temperatures reduced the fecundity rates of these insects. This study concludes that temperature deviations from the optimum cause harmful effects on the biology of bruchid and curculionid and higher temperatures during the developmental stages of insects cause rapid population build up and higher population size within short period of time, thus resulting in higher per cent of grain infestation during storage of food grains.